Node self‐connections and metapopulation persistence: reply to Saura (2018). (19th February 2018) - Zamborain‐Mason, Jessica; Russ, Garry R.; Abesamis, Rene A.; Bucol, Abner A.; Connolly, Sean R.
Abstract: Saura (2018 ) claims that studies using the Probability of Connectivity metric (PC) had already demonstrated the importance of including node self‐connections in network metrics. As originally defined and used, PC cannot test the importance of self‐connections. However, with key terms redefined, PC could be a useful tool in future work.